Antiviral effect of alpha-glucosidase inhibitors on viral morphogenesis and binding properties of hepatitis C virus-like particles. - Chapel, C; Garcia, C; Roingeard, P; Zitzmann, N; Dubuisson, J; Dwek, R; Trépo, C; Zoulim, F; Durantel, D (Microbiology Society, 2006)
Hepatitis C virus (HCV) infections are a major public-health concern. New antiviral drugs are needed urgently to complement and improve the efficacy of current chemotherapies. The morphogenesis of HCV represents an interesting, and still unexploited, novel molecular target. alpha-Glucosidase inhibitors derived from the glucose analogue deoxynojirimycin (DNJ) inhibit viral morphogenesis in cellulo via perturbation of the N-glycosylation pathway and hence the misfolding of viral glycoproteins that depend on certain N-glycans for correct folding. Due to the heavy N-glycosylation of HCV glycoproteins, it was hypothesized that such inhibitors would also affect HCV morphogenesis. To study the effect of alpha-glucosidase inhibitors on viral morphogenesis and binding properties, HCV virus-like particles (VLPs) were produced by using baculovirus loaded with HCV structural-protein genes. Here, it is demonstrated that, in the presence of these alpha-glucosidase inhibitors, viral glycoproteins synthesized and retained in the endoplasmic reticulum (i) contain unprocessed, triglucosylated N-glycans, (ii) are impaired in their interaction with calnexin and (iii) are at least partially misfolded. Moreover, it is shown that, although the production of VLPs is not affected by alpha-glucosidase inhibitors, these VLPs contain unprocessed, triglucosylated N-glycans and potentially misfolded glycoproteins. Finally, it is demonstrated that VLPs produced in the presence of alpha-glucosidase inhibitors have impaired binding properties to hepatoma cells. The inhibitors of morphogenesis studied here target steps of the HCV viral cycle that may prevent or delay viral resistance. These alpha-glucosidase inhibitors may prove to be useful molecules to fight HCV infection in combination protocols.